Resolving the heterogeneity of diaphragmatic mesenchyme: a novel mouse model of congenital diaphragmatic hernia - Louise Cleal; Sophie L. McHaffie; Martin Lee; Nick Hastie; Ofelia M. Martínez-Estrada; You-Ying Chau (The Company of Biologists, 2021)
Congenital diaphragmatic hernia (CDH) is a relatively common developmental defect with considerable mortality and morbidity. Formation of the diaphragm is a complex process that involves several cell types, each with different developmental origins. Owing to this complexity, the aetiology of CDH is not well understood. The pleuroperitoneal folds (PPFs) and the posthepatic mesenchymal plate (PHMP) are transient structures that are essential during diaphragm development. Using several mouse models, including lineage tracing, we demonstrate the heterogeneous nature of the cells that make up the PPFs. The conditional deletion of Wilms tumor 1 homolog (Wt1) in the non-muscle mesenchyme of the PPFs results in CDH. We show that the fusion of the PPFs and the PHMP to form a continuous band of tissue involves movements of cells from both sources. The PPFs of mutant mice fail to fuse with the PHMP and exhibit increased RALDH2 (also known as ALDH1A2) expression. However, no changes in the expression of genes (including Snai1, Snai2, Cdh1 and Vim) implicated in epithelial-to-mesenchymal transition are observed. Additionally, the mutant PPFs lack migrating myoblasts and muscle connective tissue fibroblasts (TCF4+/GATA4+), suggesting possible interactions between these cell types. Our study demonstrates the importance of the non-muscle mesenchyme in development of the diaphragm.